How Financial and Reputational Incentives Can Be Used to Improve Medical Care. (17th November 2015) - Roland, Martin; Dudley, R. Adams
Abstract : Objectives: Narrative review of the impact of pay‐for‐performance (P4P) and public reporting (PR) on health care outcomes, including spillover effects and impact on disparities. Principal Findings: The impact of P4P and PR is dependent on the underlying payment system (fee‐for‐service, salary, capitation) into which these schemes are introduced. Both have the potential to improve care, but they can also have substantial unintended consequences. Evidence from the behavioral economics literature suggests that individual physicians will vary in how they respond to incentives. We also discuss issues to be considered when including patient‐reported outcome measures (PROMs) or patient‐reported experience measures into P4P and PR schemes. Conclusion: We provide guidance to payers and policy makers on the design of P4P and PR programs so as to maximize their benefits and minimize their unintended consequences. These include involving clinicians in the design of the program, taking into account the payment system into which new incentives are introduced, designing the structure of reward programs to maximize the likelihood of intended outcomes and minimize the likelihood of unintended consequences, designing schemes that minimize the risk of increasing disparities, providing stability of incentives over some years, and including outcomes that are relevant to patients' priorities. In addition, because of the limitations of PR and P4P as effective interventions in their own right, it is important that they are combined with other policies and interventions intended to improve quality to maximize their likely impact.